Stereotactic body radiotherapy (SBRT) in patients with lung metastases-prognostic factors and long-term survival using patient self-reported outcome (PRO) - Kessel, Kerstin A.; Grosser, Rebekka C. E.; Kraus, Kim Melanie; Hoffmann, Hans; Oechsner, Markus; Combs, Stephanie E. (BMC Cancer, 2020)
Objectives: The present study aims to evaluate long-term side-effects and outcomes and confirm prognostic factors after stereotactic body radiotherapy (SBRT) of pulmonary lesions. This is the first work that combines the investigated data from patient charts and patient-reported outcome (PRO) up to 14 years after therapy. Materials and methods: We analyzed 219 patients and 316 lung metastases treated between 2004 and 2019. The pulmonary lesions received a median dose and dose per fraction of 35 Gy (range: 14-60.5 Gy) and 8 Gy (range: 3-20 Gy) to the surrounding isodose. During the last 1.5 years of monitoring, we added PRO assessment to our follow-up routine. We sent an invitation to a web-based survey questionnaire to all living patients whose last visit was more than 6 months ago. Results: Median OS was 27.6 months. Univariate analysis showed a significant influence on OS for KPS ≥90%, small gross tumor volume (GTV) and planning target volume (PTV), the absence of external metastases, ≤3 pulmonary metastases, and controlled primary tumor. The number of pulmonary metastases and age influenced local control (LC) significantly. During follow-up, physicians reported severe side-effects ≥ grade 3 in only 2.9% within the first 6 months and in 2.5% after 1 year. Acute symptomatic pneumonitis grade 2 was observed in 9.7%, as grade 3 in 0.5%. During PRO assessment, 39 patients were contacted, 38 patients participated, 14 participated twice during follow-up. Patients reported 15 cases of severe side effects (grade ≥ 3) according to PROCTCAE classification. Severe dyspnea (n = 6) was reported mostly. Conclusion: We could confirm excellent local control and low toxicity rates. PROs improve and complement follow-up care. They are an essential measure in addition to the physician-reported outcomes. Future research must be conducted regarding the correct interpretation of PRO data.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Lung metastasis; Outcomes; Patient-reported outcome; PRO; SBRT; Stereotactic body radiotherapy; Survival; Toxicity